2015
DOI: 10.1063/1.4912834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the project timeliness with fuzzy constraints

Abstract: This paper concerns to the RCPS problem with imprecise activity duration times and flexible constraints. Schedule input data and constraints are modeled by fuzzy numbers. Fuzzy RCPS problem is based on the concept of pair-wise dominance between two fuzzy numbers and solved with the use of simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Similar analyzes should be conducted for other risk factors. What's more, thanks to the use of linguistic variables, it is possible to use the results of the analysis in fuzzy decision models [10]. Such application of the analysis will translate into a significant improvement in the forecasting of disturbances and difficulties related to conducting construction works.…”
Section: Discussionmentioning
confidence: 99%
“…Similar analyzes should be conducted for other risk factors. What's more, thanks to the use of linguistic variables, it is possible to use the results of the analysis in fuzzy decision models [10]. Such application of the analysis will translate into a significant improvement in the forecasting of disturbances and difficulties related to conducting construction works.…”
Section: Discussionmentioning
confidence: 99%
“…Successful completion of a construction project means that its completion has been completed within the assumed budget, at the scheduled time, in accordance with the expected quality, and taking into account all investor requirements. In the literature, many studies can be found regarding the analysis of construction projects due to their costs (Juszczyk, Leśniak & Zima, 2018;Wieczorek, Plebankiewicz & Zima, 2019), time (Ibadov & Kulejewski, 2015;Krzemiński, 2017), organizational aspects (Hoła, 2015;Kozlovska, Mackova & Spisakova, 2016;Lendo-Siwicka, Połoński & Pawluk, 2016;Nowotarski, Pasławski & Matyja, 2016;Grzyl, Miszewska-Urbańska & Apollo, 2017;Nowogońska & Cibis, 2017;Hanak & Korytarova, 2018), safety issues (Hoła & Szóstak, 2015), or the use of innovative solutions in construction fi led (Mrówczyńska, 2011;Kapliński, 2018). Yet, it is the calculation of costs that is one of the most important aspects of construction projects, both from the investor's and contractor's point of view.…”
Section: Introductionmentioning
confidence: 99%
“…There are many papers devoted to the analysis of construction projects in terms of time [16,24], costs [18,28,32,40], logistics [43], process organizational aspects [12,13,14,19,22,26,37,38], work safety [15], innovative solutions [19] and project contracting [23]. There are many factors affectingthe course of a construction project in time, and frequently they can be foreseen already at the works planning stage.…”
Section: Introductionmentioning
confidence: 99%